2015
DOI: 10.1016/j.ijhydene.2015.08.107
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of H2 adsorption on metal-doped graphene sheets with nitrogen-substituted defects

Abstract: a b s t r a c tIn the present work, we perform a theoretical study of light metal (Li, Na, and Ca) doping and H 2 adsorption on graphene sheets with N-substituted defects. Through density functional theory calculations, the adsorption energies, density of states, and extent of charge transfer in systems featuring H 2 adsorption on metal-doped species (ideal, pyridinic, and pyrrolic graphene sheets) are obtained, and we determine that both N and metal atoms play important roles in H 2 adsorption. In addition, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…The HA-2 sample also presented the highest H 2 uptake of all analyzed samples: 12.1 mg g −1 at 77 K and 1 bar (Table 2). Although the H 2 uptake value of HA-2 was much lower than the U.S. Department of Energy (DOE) target of 65 mg g −1 (at present, no experimental H 2 storage materials meet the requirements for practical applications set by the U.S. DOE), HA-2 exhibited ultrahigh H 2 adsorption efficiency, as indicated by the uptake per unit specific surface area of 1.14 × 10 −3 wt % m 2 g −1 , which was close to the upper limit of H 2 adsorbed in a monolayer [34].…”
Section: Resultsmentioning
confidence: 99%
“…The HA-2 sample also presented the highest H 2 uptake of all analyzed samples: 12.1 mg g −1 at 77 K and 1 bar (Table 2). Although the H 2 uptake value of HA-2 was much lower than the U.S. Department of Energy (DOE) target of 65 mg g −1 (at present, no experimental H 2 storage materials meet the requirements for practical applications set by the U.S. DOE), HA-2 exhibited ultrahigh H 2 adsorption efficiency, as indicated by the uptake per unit specific surface area of 1.14 × 10 −3 wt % m 2 g −1 , which was close to the upper limit of H 2 adsorbed in a monolayer [34].…”
Section: Resultsmentioning
confidence: 99%
“…The second stage, the Shift depicted in Fig. 3 between points (6)(7)(8)(9)(10)(11)(12), is designed to reduce the concentration of CO in the emissions generated in the first stage [40]. To achieve a reduction in CO concentration, two catalysts are placed in series, producing exothermic reactions that cause CO 2 emissions.…”
Section: Lng Vessel With Dual-fuel Diesel Electric Propulsion and H 2 Generationmentioning
confidence: 99%
“…( 2) below, where coefficients h, i, j, k and l represent the molar composition of the mixture. The second stage, (10)(11), is performed in a copper zinc catalyst at a temperature of 200°C [31,37], obtaining CO concentration values of around 0.2-0.3% (wet basis) at the reformer outlet. This process is based on Eq.…”
Section: Lng Vessel With Dual-fuel Diesel Electric Propulsion and H 2 Generationmentioning
confidence: 99%
“…Ao and Peeters showed that N-doped and applying an electric field have catalytic effects on the hydrogenation of carbon nanostructures, which can be a promising HS media with reversible hydrogen adsorption/desorption [14,15,38]. By means of DFT calculations, Rao et al have studied Ca-doped N-substituted defective graphene and its potential application in H 2 storage [27]. They determined that the N-edged defects in graphene can enhance the binding energy of metals [27].…”
Section: Introductionmentioning
confidence: 99%
“…By means of DFT calculations, Rao et al have studied Ca-doped N-substituted defective graphene and its potential application in H 2 storage [27]. They determined that the N-edged defects in graphene can enhance the binding energy of metals [27]. Furthermore, Mananghaya showed that the N-doped CNT enhanced chemical functionalization of all TMs suggesting a considerable reduction of clustering of metal atoms over the metal decorated nanotube.…”
Section: Introductionmentioning
confidence: 99%